Flower-like BiOBr/UiO-66-NH2 nanosphere with improved photocatalytic property for norfloxacin removal. (April 2019) - Yang, Zhiquan; Tong, Xiaowen; Feng, Jinna; He, Shan; Fu, Mingli; Niu, Xiaojun; Zhang, Taiping; Liang, Heng; Ding, An; Feng, Xiaochi
Abstract: Metal–organic frameworks (MOFs) have attracted widespread concerns in the photocatalysis research. However, MOFs-based photocatalyts for antibiotics treatment are still very limited. There are also few reports on selecting MOFs as supports to regulate the morphology of Bismuthoxyhalides. In this study, BiOBr/UiO-66-NH2 composites with three-dimensional structure of flower-like nanosphere were fabricated via a facile synthetic route. Various characterizations, such as XRD, SEM and XPS, proved the successful synthesis of composite and revealed that BiOBr nanoplates grow on the surfaces of the UiO-66-NH2 with an intimate interaction. A typical fluoroquinolones antibiotics, norfloxacin (NOR) was selected to estimate the photocatalytic efficiency of the BiOBr/UiO-66-NH2 complex. A series of the composites all exhibited higher NOR removal performance than the pure components and mechanically mixed sample under simulated sunlight. Among them, the composite with UiO-66-NH2 content of 20 w% (BUN-20), had good structural stability and the best performance on the removal of NOR. The removal efficiency of NOR (10 mg/L) over BUN-20 (0.3 g/L) was 93.60% within 180 min irradiation. Three factors during the fabricating process, such as increased surface active sites, improved photoadsorption capacity and lower recombination probability of electron-hole pair might be accountable for the meliorative photocatalytic performance. Ultimately, a plausible photocatalytic mechanism was also proposed. Graphical abstract: Image 1 Highlights: Flower-like BiOBr/UiO-66-NH2 were fabricated via a facile synthetic route. Modified BiOBr with UiO-66 had enhanced activity for NOR removal. BET, optical absorption and electron-hole pair improved photocatalytic performance. Photocatalytic mechanism of NOR was proposed.